Pengaruh Perbedaan Metode Ekstraksi Maceration dan Microwave Assisted Extraction (MAE) Terhadap Penetapan Kadar Flavonoid Total Buah Ara (Ficus racemosa L.) - Andry, Muhammad; Ligo, Azzura; Anggi, Reza Destri; Pradita, Diding; Luthvia, Luthvia; Nasution, Muhammad Amin; Pertiwi, Nia Novranda; Arifin, Arfiani (Journal of Pharmaceutical and Sciences, 2025)
Figs (Ficus racemosa L.) are an essential source of bioactive components such as phenols, terpenoids, flavonoids, and alkaloids with antioxidant properties. Two extraction methods are used to extract flavonoids from figs: conventional and non-conventional. This study aimed to determine the effect of different extraction methods—maceration and Microwave Assisted Extraction (MAE)—on the total flavonoid content in figs (Ficus racemosa L.). The research was conducted using a laboratory experimental method. The procedures included collecting and preparing plant materials, producing simplicia, evaluating simplicia characteristics, conducting phytochemical screening, preparing extracts, and determining total flavonoid content. The results showed that the maximum wavelength of quercetin was 438 nm, with a regression equation of Y = 0.0669x + 0.0084. The average absorbance values of fig extract using the maceration method were 0.216 with methanol, while the MAE method was 0.280 with methanol. The average percentage of flavonoid content using the maceration method was 0.1245% with methanol, while with the MAE method, it was 0.1623% with methanol. The total flavonoid content of fig extract using the maceration method was 1.2451 mgQE/g extract with methanol, while with the MAE method, it was 1.6238 mgQE/g extract with methanol. The study concluded that the highest total flavonoid content was found in the methanol extract obtained through MAE. This extract had a value of 1.6238 mgQE/g extract.